2018
DOI: 10.1007/s10964-018-0862-1
|View full text |Cite
|
Sign up to set email alerts
|

Explicating Acculturation Strategies among Asian American Youth: Subtypes and Correlates across Filipino and Korean Americans

Abstract: Acculturation strategy, a varying combination of heritage and mainstream cultural orientations and one of the significant determinants of youth development, has been understudied with Asian American youth and particularly at a subgroup-specific level. This study used person-oriented latent profile analysis (LPA) to identify acculturation strategy subtypes among Filipino American and Korean American adolescents living in the Midwest. Associations between the subtypes and numerous correlates including demographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 99 publications
(158 reference statements)
2
35
0
Order By: Relevance
“…A similar pattern was found in a study with a significant proportion of Southeast Asian Americans that identified promotion of mistrust as a protective factor (Thai et al, 2017). In addition, FA youth, compared with KA youth, report a stronger sense of affiliation to the mainstream society (Choi et al, 2018).…”
Section: Social Positionssupporting
confidence: 81%
See 1 more Smart Citation
“…A similar pattern was found in a study with a significant proportion of Southeast Asian Americans that identified promotion of mistrust as a protective factor (Thai et al, 2017). In addition, FA youth, compared with KA youth, report a stronger sense of affiliation to the mainstream society (Choi et al, 2018).…”
Section: Social Positionssupporting
confidence: 81%
“…In addition, youth participants who completed 95% or more of the survey were automatically entered into a lottery for a $100 gift card (a total of 40 and 20 gift cards in Waves 2 and 3, respectively). More details about the recruitment procedures are found elsewhere (Choi et al, 2018).…”
Section: Recruitment and Proceduresmentioning
confidence: 99%
“…Therefore, Korean mothers may perceive less need or motivation to engage themselves in the larger mainstream culture, and maintain strong endorsement of their heritage culture and great involvement in Korean cultural practices (i.e. psychological and behavioral separation; Choi et al, 2018).…”
Section: Differences Between Psychologically-separated Cims and Kimsmentioning
confidence: 99%
“…This study has offered insights into the rapid expansion of international schooling worldwide (Brummitt & Keeling, 2013; ISC Research, 2019), fuelled by demand from host-country parents (Bunnell, 2019), by offering insights into why host-country parents choose this system of schooling and some of the consequences of their choice. The study has focused on Bahraini parents choosing international schools, but these findings may also be useful for understanding school choices in other contexts – for example, for examining other contexts where parents are choosing non-government systems of schooling, and also for understanding school choices in other contexts where there is a cultural difference between the parent community and the predominant culture of a school (see, for example, Choi et al, 2018; Petreñas et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…According to Berry, there are four different strategies that individuals can take as this contact occurs: integration (maintaining own culture while participating in the other); assimilation (abandoning own culture in favour of the other); separation (maintaining own culture and rejecting participation in the other); and marginalisation (losing the ability to identify with either culture). The concept of acculturation strategies is useful for understanding how individuals respond to a different culture, and has been used extensively to understand student behaviours, with the focus being on how students from ethnic minority and/ or migrant backgrounds adjust to the different social norms of the dominant group at their school (see, for example, Choi et al, 2018; Petreñas et al, 2021). However, very little attention has been paid to understanding the behaviours of parents in terms of acculturation, with one salient exception being the work of Pirchio et al (2017) for whom it is used incidentally in their study of the parental involvement of parents from immigrant and non-immigrant backgrounds.…”
Section: Literature Reviewmentioning
confidence: 99%